Material Requipment Planning Untuk Penentuan Harga Pokok Produksi Pada PT Philnesia International - M Munifah; Eko Siswanto; Novi Sri Setiyawati (Universitas Sains dan Teknologi Komputer, 2020)
PT Philnesia International is a limited liability company engaged in the business of manufacturing furniture products. At PT Philnesia International, if an order is received by the company, then the company makes products in accordance with existing orders. Control and planning of raw materials are very important in the production process so that the production process can run smoothly, on time and can reduce delays in delivery. PT Philnesia International wants to create a computerized Production Accounting Information System. In addition to making it more effective, accurate and efficient, the owner wants to make it easier for his employees to perform more advanced and modern and makes it easier to view reports every day. The results that will be obtained from the design of this system is an information system that can make it easier for companies to determine raw material requirements, the production process and view the required reports.